Peningkatan Kesadaran Higienis Tangan dan Mulut di Wilayah Dukuh Jetis, Trimurti, Srandakan, Bantul - Basil, Abdulloh Sahmul; Ahnaf, Adiba Fahrial; Ilyasa, Alya; Alam, Dhiya Falah; Herman, Jhalu Rizkina; Khairunnisa, Nadia; Fahreza, Naufal Muhammad Agna; Riyantini, Nuril Najah; Arsani, Salwa Nabilah Onidya; Rahiimah, Qeismawati; Arsito, Puguh Novi (Universitas Muhammadiyah Yogyakarta, 2025)
Personal hygiene is an activity carried out by individuals to improve comfort, quality of life, and body health. This effort is carried out to ensure individual comfort and health by maintaining and taking care for personal hygiene. Personal hygiene includes maintaining the health of the body, such as hands and oral hygiene, which can be implemented through Clean and Healthy Living Behavior (PHBS). Clean and healthy living behaviors play a crucial role in the prevention of various diseases, such as diarrhea, worms, dental caries, and other infectious diseases that can be transmitted through hands. Therefore, education about PHBS is very necessary so that this behavior can be applied and become a habit in daily life. However, there are still many bad habits in maintaining personal hygiene, especially hand and mouth hygiene among children and the people of Dukuh Jetis, Trimurti, Srandakan, Bantul. Based on these problems, the community engagement program of Universitas Muhammadiyah Yogyakarta focuses on increasing hand and oral hygiene awareness in Dukuh Jetis. The purpose of this program is to increase awareness of PHBS, especially hands and mouths in children and empower PKK (Family Welfare Empowerment) mothers through homemade soap making training as an effort to increase access to hygiene in the household. The method used is counseling with active interaction to students of Al-Aysar IT Kindergarten and Elementary School which is carried out by demonstrating how to wash hands in 6 steps and how to brush teeth correctly. Meanwhile, the training on making homemade soap was carried out with an explanation of the material and continued with group practice using simple ingredients to make soap. The results of the community service program in PHBS counseling activities can be seen from the increase in the understanding rate of Kindergarten and Elementary School IT Al-Aysar Dukuh Jetis students who were tested before the program, namely the average pretest was 74.6 with the results tested after the program, namely the average posttest was 76.5. In the Homemade Soap Making Training activity, a pretest with an average result of 50.9 and a posttest with an average result of 78.6 was carried out. There was an increase in the understanding of counseling and training participants as seen from the results of the pretest and posttest conducted before and after the activity was carried out.